Strategies of LncRNA DLX6-AS1 on Study and Therapeutics - Zhao, Yanyan; Li, Pei (Frontiers in Genetics, 2022)
Accumulating evidences have revealed the vital regulatory roles of lncRNA DLX6-AS1 in various tumors on pre-transcriptional, transcriptional and post-transcriptional levels, and the existence in the exosomes of peripheral blood from patients with tumors, which makes it the potential prognosis factor and therapeutic target. However, most of literatures are devoted to studying the effect of lncRNA DLX6-AS1 as a sponging molecular of miRNAs, the research of which is likely to stick into a dilemma. Besides, literatures published already have demonstrated an exciting cell malignant phenotype inhibition with knockdown of lncRNA DLX6-AS1 in various tumor cell lines. With the comprehensive development of the delivery systems, high-throughput sequencing and aptamer, the problems of how to find novel research methods and exploring the therapeutic ways which are based on lncRNA DLX6-AS1 in vivo could come into a period to deal with. This review aims to summary the research situations of lncRNA DLX6-AS1 and try to discuss its other possible study methodologies and therapeutic strategies, which are hoped to help with the development of the research of lncRNA DLX6-AS1 and the transformation from basic to clinical research.